Human-algorithm collaboration: Achieving complementarity and avoiding unfairness - Donahue, Kate; Chouldechova, Alex; Kenthapadi, Krishnaram (2022 ACM Conference on Fairness, Accountability, and Transparency, 2022)
Much of machine learning research focuses on predictive accuracy: given a task, create a machine learning model (or algorithm) that maximizes accuracy. In many settings, however, the final prediction or decision of a system is under the control of a human, who uses an algorithm’s output along with their own personal expertise in order to produce a combined prediction. One ultimate goal of such collaborative systems is complementarity: that is, to produce lower loss (equivalently, greater payoff or utility) than either the human or algorithm alone. However, experimental results have shown that even in carefully-designed systems, complementary performance can be elusive. Our work provides three key contributions. First, we provide a theoretical framework for modeling simple human-algorithm systems and demonstrate that multiple prior analyses can be expressed within it. Next, we use this model to prove …